MEASURING FINANCIAL BEHAVIOR MILLENNIAL AND GENERATION Z IN INDONESIA: ANALYSIS APPROACHED THAT ENSURE FINANCIAL RESILIENCE IN THE FACE OF POTENTIAL CRISIS - Maladianti, Devi
This study explores financial literacy, behavior and preparedness of Millennials and Gen Z in Indonesia, focus on understanding how those three factors interact with job status income allocation, debt management and digital engagement. The increasing dependency on digital financial tools is also underlined, this research purpose is to assess the extending younger generation in preparing to manage their finance for future financial security. A quantitative research design is employed, involving a sample of 219 respondents drawn from a population of 222 individuals aged 20 to 60 years old. Data were collected using a structured questionnaire and analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM).